Symptomatic female carriers of Duchenne Muscular Dystrophy (DMD): genetic and clinical characterization - Giliberto, Florencia (2014)
Duchenne muscular dystrophy (DMD) is an X-linked recessive disease caused by mutations in the dystrophin gene and is characterized by muscle degeneration and death. DMD affects males; females being asymptomatic carriers of mutations. However, some of them manifest symptoms due to a translocation between X chromosome and an autosome or to a heterozygous mutation leading to inactivation of most of their normal X chromosome. Six symptomatic female carriers and two asymptomatic were analyzed by: I) Segregation of STRs-(CA)n and MLPA assays to detect a hemizygous alteration, and II) X chromosome inactivation pattern to uncover the reason for symptoms in these females. The symptomatic females shared mild but progressive muscular weakness and increased serum creatin kinase (CK) levels. Levels of dystrophin protein were below normal or absent in many fibers. Segregation of STRs-(CA)n revealed hemizygous patterns in three patients, which were confirmed by MLPA. In addition, this analysis showed a duplication in another patient. X chromosome inactivation assay revealed a skewed X inactivation pattern in the symptomatic females and a random inactivation pattern in the asymptomatic ones. Our results support the hypothesis that the DMD phenotype in female carriers of a dystrophin mutation has a direct correlation with a skewed X-chromosome inactivation pattern.